Religious Court Judges’ Ratio Decidendi on Excessive Murabahah Penalties: A Rawlsian Analysis - Aji Saifulloh Aji; Muhammad Fakhril Umam (UIN Mahmud Yunus Batusangkar, 2026)
This study analyzes the judges’ ratio decidendi in Decision Number 156/Pdt.G/2024/PA.Smn concerning the imposition of late-payment penalties exceeding the principal amount in a murabahah financing contract and examines its conformity with John Rawls’ theory of justice. This normative legal research employs case and conceptual approaches. The primary legal material is Decision Number 156/Pdt.G/2024/PA.Smn, while secondary materials consist of DSN-MUI Fatwas and relevant scholarly literature. Data were analyzed qualitatively through legal interpretation of the judges’ reasoning and the principles of justice underlying the decision. The findings show that the judges’ ratio decidendi was based on the principle of pacta sunt servanda, emphasizing contractual legal certainty and the binding force of agreements. Consequently, the court ordered the payment of the remaining financing obligation of Rp209,700,000 and a late-payment penalty of Rp226,800,000. However, from the perspective of John Rawls’ theory of justice, the decision does not fully reflect substantive justice because it inadequately considers the defendants’ economic hardship caused by the Covid-19 pandemic. The decision therefore reflects legal-formal justice and highlights the need to balance legal certainty, proportionality, and protection of vulnerable parties in resolving Islamic economic disputes.